A Review on Dynamic Network Using Flexible Active-Mode Period Scheme for Telemedicine - Iyobhebhe, Matthew; Yaro, A S; Bello, Habeeb; Agbon, E E; Al-Mustapha, M D; Kabir, M T; Salihu, Siyaka O (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2023)
Challenges associated with transmitter node during the process of intelligent transceiver nodes attempting to be active state after receiving a message outside its time slot schedule which might result in energy depletion through receiver node are the most notable origin of excessive energy consumption in the system. Various methods have been carried out to minimize the overhead cost. In this article, we presented the Dynamic Network using Adaptive Wake-Up Interval Media Access Control (MAC) protocol for Wireless Body Area Networks (WBANs) for telemedicine which could lead to the minimization of the energy consumption in the network and maximization of network lifetime. A Receiver Controlled mechanism balances the number of wake-up periods between Receiver node and Transmitter nodes and estimation of traffic load. This article depicts no earlier examination of dynamic network using Flexible Active-Mode period scheme-based media access control protocol for WBAN. Therefore, this review work could lead to the improvement of dynamic network Flexible Active-Mode –media access control protocols and invigorate a clearer way of finding AWI-Media Access Control protocol problems.